Development of an Interactive E-Comic Based on Digital Literacy for Contextual English Learning in Elementary Schools - Chandra Anugrah Putra; Bulkani Bulkani; Heru Nurochman; Muhammad Andi Setiawan (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2025)
Background: The integration of digital literacy into English language learning for elementary school students remains a challenge, as existing media often lack interactivity and contextual engagement. This study addresses the need for innovative and motivating instructional media by transforming previous printed e-comic research into an interactive digital learning tool. Aim: The study aims to develop and evaluate an interactive e-comic that combines visual, textual, auditory, and simple animation elements to enhance English vocabulary mastery and learning motivation among elementary school students. Method: This research applied a Research and Development (R&D) design consisting of need analysis, design, development, limited testing, and evaluation. Data were collected through expert validation, questionnaires, observations, and interviews involving English teachers and students in grades 3 to 6. Quantitative data were analyzed descriptively using percentage scores, while qualitative data were analyzed through thematic interpretation. Results and Discussion: The developed interactive e-comic received an excellent feasibility rating from material and media experts, as well as positive responses from users. The trial results showed that the media improved students’ vocabulary retention, reading comprehension, and engagement. The integration of audio-visual features and interactive storytelling supported multimodal learning and enhanced students’ digital literacy competencies. Furthermore, the product demonstrated strong potential for educational commercialization through subscription-based models and institutional licensing. Conclusion: The interactive e-comic effectively enhances English learning outcomes and digital literacy skills among elementary students, providing an engaging, accessible, and pedagogically sound learning tool aligned with the Merdeka Curriculum. This innovation contributes to the advancement of digital-based English education and supports the development of adaptive learning environments in primary schools.